2006
DOI: 10.2166/wst.2006.856
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community change of sulfate reduction and sulfur oxidation bacteria in the activated sludge cultivated with acetate and peptone

Abstract: The growth of sulfate reducing bacteria (SRB) and filamentous sulfur bacteria was monitored on a laboratory scale in activated sludge reactors using acetate and peptone as the artificial wastewater. When the artificial wastewater contained acetate and peptone, filamentous bacteria increased in the sludge and the SVI values increased. There was a good correlation between sulfate reducing activity and sulfur oxidation activity in the produced sludge. The microbial community change of filamentous sulfur bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…3, Thiothrix was the main taxon affecting the settling properties. This is in agreement with previous studies where extreme filamentous bulking was provoked by Thiothrix (SVI>600 mg/L, Yamamoto-Ikemoto et al, 1991;Miyazato et al, 2006). As suggested by Fig.…”
Section: Sludge Settling Propertiessupporting
confidence: 93%
“…3, Thiothrix was the main taxon affecting the settling properties. This is in agreement with previous studies where extreme filamentous bulking was provoked by Thiothrix (SVI>600 mg/L, Yamamoto-Ikemoto et al, 1991;Miyazato et al, 2006). As suggested by Fig.…”
Section: Sludge Settling Propertiessupporting
confidence: 93%
“…The highest maximum specific sulfide generation activity in the presence of peptone is 3 times lower than the one in which acetate is used as electron donor with the same inoculum, demonstrating, once again, the superior efficiency of acetate as substrate. Miyazato and coworkers illustrated the existence of SRB in an activated sludge cultured with peptone with a biogenic activities between 7.2 and 19.2 mg SO 2− 4 g −1 d −1 which is comparable with the results obtained in this research work with the sediments of the facultative lagoon of the WWTP in Cuenca [16].…”
supporting
confidence: 87%
“…Practically all other inocula evaluated (with exception of the discharge sludge of the WWTP in Quito) present maximum specific sulfide production or sulfate reduction activities half the value obtained with the sediments of the natural lagoon which were 4. 16 d −1 ) with the sediments of the natural lagoon. This difference suggests that the microbial consortium present in the sediments of the natural lagoon do not have a microbial lactate oxidizing activity as efficient as in the case of the mentioned studies.…”
mentioning
confidence: 99%
“…Mixed liquor suspended solids (MLSS) and sludge volume index (SVI) of the activated sludge collected from AN2 were measured. Batch experiments were conducted to examine the sulfur oxidizing rate and sulfate reducing rate according to Miyazato et al [9]. In the sulfur oxidizing batch test, the activated sludge was centrifuged, and we adjusted the MLSS concentration by adding substrate.…”
Section: Sampling In Wwtpsmentioning
confidence: 99%
“…It was reported that sulfate reduction is the main trigger for the growth of filamentous sulfur bacteria in the AO process [8,9]. Moreover, Yamamoto-Ikemoto et al conducted batch experiments using activated sludge from a municipal WWTP and reported that phosphorus release from the sludge, which had high sulfate reduction activity, tended to be lower than that of low-activity sludge [10].…”
Section: Introductionmentioning
confidence: 99%